The philosophy of the sixteenth and seventeenth centuries - Popkin, Richard H. (Richard Henry), 1923-2005 (New York : Free Press, 1966)
Publisher Summary 1 A short anthology of philosophers of the sixteenth and seventeenth century, covering philosophical writings from Europe in the sixteenth and seventeenth centuries. Featuring writings by: Martin Luther, Francis Bacon, Rene Descartes, Thomas Hobbes, Baruch Spinoza, Amerigo Vespucci, and more.
Amerigo Vespucci -- Desiderius Erasmus -- Martin Luther -- Nicolaus Copernicus -- Johannes Kepler -- Galileo Galilei -- Michel De Montaigne -- Francis Bacon -- Pierre Gassendi -- Rene Descartes -- Thomas Hobbes -- Blaise Pascal -- Baruch Spinoza -- Nicolas Malebranche -- Gottfried Wilhelm Von Leibniz -- Pierre Bayle
Includes bibliographical references (pages 357-360)
Keywords: Philosophy